3D finite element modelling of force transmission and particle fracture of sand. (February 2018) - Imseeh, Wadi H.; Alshibli, Khalid A.
Abstract: Global compressive loading of granular media causes rearrangements of particles into a denser configuration. Under 1D compression, researchers observed that particles initially translate and rotate which lead to more contacts between particles and the development of force chains to resist applied loads. Particles within force chains resist most of the applied loads while neighbor particles provide lateral support to prevent particles within force chains from buckling. Several experimental and numerical models have been proposed in the literature to characterize force chains within granular materials. This paper presents a 3D finite element (FE) model that simulates 1D compression experiment on F-75 Ottawa sand. The FE mesh of particles closely matched 3D physical shape of sand particles that were acquired using 3D synchrotron micro-computed tomography (SMT) technique. The paper presents a quantitative assessment of the model, in which evolution of force chains, fracture modes, and stress-strain relationships showed an excellent agreement with experimental measurements reported by Cil et al. Alshibli (2017).